Granzyme B inhibits vaccinia virus production through proteolytic cleavage of eukaryotic initiation factor 4 gamma 3. - Marcelo Marcet-Palacios (Public Library of Science (PLoS), 2011)
Cytotoxic T lymphocytes (CTLs) are the major killer of virus-infected cells. Granzyme B (GrB) from CTLs induces apoptosis in target cells by cleavage and activation of substrates like caspase-3 and Bid. However, while undergoing apoptosis, cells are still capable of producing infectious viruses unless a mechanism exists to specifically inhibit viral production. Using proteomic approaches, we identified a novel GrB target that plays a major role in protein synthesis: eukaryotic initiation factor 4 gamma 3 (eIF4G3). We hypothesized a novel role for GrB in translation of viral proteins by targeting eIF4G3, and showed that GrB cleaves eIF4G3 specifically at the IESD(1408)S sequence. Both GrB and human CTL treatment resulted in degradation of eIF4G3 and reduced rates of translation. When Jurkat cells infected with vaccinia virus were treated with GrB, there was a halt in viral protein synthesis and a decrease in production of infectious new virions. The GrB-induced inhibition of viral translation was independent of the activation of caspases, as inhibition of protein synthesis still occurred with addition of the pan-caspase inhibitor zVAD-fmk. This demonstrated for the first time that GrB prevents the production of infectious vaccinia virus by targeting the host translational machinery.